135 lat Politechniki Charkowskiej - Gutnyk, Maryna; Chrzan, Krystian Leonard (Politechniki Gdańskiej, 2020)
W pracy opisano 135 letnią historię Politechniki Charkowskiej, jednej z najstarszych uczelni technicznych Imperium Rosyjskiego i niepodległej Ukrainy. Po zniesieniu pańszczyzny w Rosji w 1861 roku powstały warunki do rozwoju przemysłu. Brak kadry technicznej spowodował konieczność zorganizowania uczelni technicznych. Profesorowie Politechniki Charkowskiej stanowili trzon kadry młodszych Politechnik w Imperium Rosyjskim i ZSRR.

The paper presents the 135 years long history of Kharkiv University of Technology, one of the oldest Technical University in Russian Empire and independent Ukraine. After abolition of the serfdom in Russia in 1861, the conditions for industrial development arose. The lack of technical staff caused the necessity to organize technical universities. Professors of the Kharkiv Polytechnic constituted the core of the staff of the younger Polytechnics in Russian Empire and the USSR.
135 years of Kharkiv Polytechnic
Keywords: Instytut Molnia; generatory udarowe; kompatybilność elektromagnetyczna; National Technical University "Kharkiv Polytechnic Institute"; Molnia Institute; impulse generators; electromagnetic compatibility